A EXTENSÃO COMO ATIVIDADE FORMATIVA DE PROFESSORES E ESTUDANTES E QUALIFICADORA DO ENSINO - Frison, Marli D.; Boff, Eva T. d. O.; Busnello, Maristela B.; Ferreira, Francesca W.; Cavinatto, Mariluci; Martins, Vanessa B. (Salão do Conhecimento, 2013)
Resumo